Co(III) as Mediator in Phenol Destruction Using Electrochemical Oxidant - Herlina Herlina; Derlini Derlini; Muhammad Razali (UPT Penerbitan Universitas Jember, 2016)
Electrochemically processing for organic waste treatment has been developed widely because the advantages of low cost, efficient, the exhausted gas that does not contain toxic materials, and can be operated in a relative low temperature. Electrochemical oxidation of organic compounds using metal ion mediator is one alternative method that is appropriate for the management of organic waste. Cobalt (III) is a strong oxidizing agent is prepared by the electrochemical oxidation method and as a mediator in the process of mediated electrochemical oxidation. At potential of 6 volt, with 4 M nitric acid and temperature of 25°C give result 23.86% where Co (II) is converted to Co (III) within 2 hours of the initial concentration of Co (II) 0.1 M. The addition of AgNO3 to catholyte can increase the concentration of Co (III). At the optimum conditions, the mediator metal ion Co (III) can destructed to 66.44% of phenol compounds are oxidized to CO2 for two hours.